Security in Industry 4.0 : Cyber-attacks and countermeasures - et. al., Aziz Naanani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Industry 4.0 or the smart factory is a concept that aims to improve productivity and organize the means of production. Industry 4.0 introduces a new way of communication in which products and machines are connected to a computer network. Plant components can communicate locally (local area network) as they can communicate internationally (wide area network). Industry 4.0 has therefore created a globally interconnected system in which maintenance and optimization can be conducted autonomously based on artificial intelligence and the Internet of Things (IoT). While it is true that relying on computer networks in today's factories will allow them to have better control, however this will make them vulnerable to attacks that can threaten the economy or the security of a country , and here we are talking about cyber attacks . In this article we will discuss the different cyber threats to the smart factory, their impacts and possible countermeasures